Wounded heart : hope for adult victims of childhood sexual abuse hope for adult victims of childhood sexual abuse - Allender, Dan B. (Colorado Springs, Colo. : NavPress, 2008)
"Sexual abuse knows no religious or social boundaries. The Wounded Heart is an intensely personal and specific look at this form of abuse. Dr. Allender explores the secret lament of the soul damaged by sexual abuse and lays hold of the hope buried there by the One whose unstained image we all bear. Includes information about false memory issues."--Publisher description.
Prologue: the quest for a cure -- Preface: a question of memory -- pt. 1. The dynamics of abuse. The reality of a war : facing the battle ; The enemy : sin and shame ; Deflection : the clash with contempt ; The war zone : strategies for abuse -- pt. 2. The damage of abuse. Powerlessness ; Betrayal ; Ambivalence ; Secondary symptoms ; Style of relating -- pt. 3. Prerequisites for growth. The unlikely route to joy ; Honesty ; Repentance ; Bold love ; Epilogue : words to the wise.
Includes bibliographical references (pages 267-270).
Keywords: Child sexual abuse; Child sexual abuse -- Religious aspects -- Christianity; Adult child sexual abuse victims; Incest victims; Adult child sexual abuse victims; Child sexual abuse; Child sexual abuse -- Religious aspects -- Christianity; Incest victims